2004
DOI: 10.1017/s1355617704103111
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral volume loss, cognitive deficit and neuropsychological performance: Comparative measures of brain atrophy: I. Dementia

Abstract: There are several magnetic resonance (MR) imaging methods to measure brain volume and cerebral atrophy; however, the best measure for examining potential relationships between such measures and neuropsychological performance has not been established. Relationships between seven measures of MR derived brain volume or indices of atrophy and neuropsychological performance in the elderly subjects of the population-based Cache County, Utah Study of Aging and Memory (n = 195) were evaluated. The seven MR measures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 54 publications
2
61
1
2
Order By: Relevance
“…Some researchers use structure volume as the dependent variable, while others use volume ratios; some advocate using intracranial volume (ICV) as a covariate, while others do not. We conducted analyses on age and gender using each of these methods, and report them all in order to facilitate comparisons (see [3,4 for similar approaches). Table 1 presents the demographics of our sample and the number of scans that were available for each brain structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers use structure volume as the dependent variable, while others use volume ratios; some advocate using intracranial volume (ICV) as a covariate, while others do not. We conducted analyses on age and gender using each of these methods, and report them all in order to facilitate comparisons (see [3,4 for similar approaches). Table 1 presents the demographics of our sample and the number of scans that were available for each brain structure.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the rate of volume change in gray and white matter tissue, cerebrospinal fluid, and lesions, as well as the caudate, putamen, and hippocampus. We sought to address several issues (for a similar approach, see [4]): Can we provide precise, quantitative estimates of brain atrophy, laterality, and gender differences? In particular, what is the relation between white-matter decline and aging in an older population?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio approach corrects for head size on an individual basis (Sanfilipo et al 2004) and has been utilized in previous studies of SH Haley et al 2007;Lane et al 2011;Opherk et al 2014). Previous research comparing this approach with other standardization techniques has revealed minimal to no differences in results, with no statistically superior standardization measure (Bigler et al 2004;Tate et al 2011). …”
Section: Neuropsychological Testingmentioning
confidence: 99%
“…The relatively large number of both controls and patients in our study resulted in greater statistical power, and to improve this further we measured the total intracranial volume (TICV) and used it to eliminate some of the normal population variance in CSA. The TICV is not affected by MS, and was used for normalization purposes in several previous atrophy studies (9,15,16,23,24). We also estimated the statistical power of the study, and the increase in power due to the normalization.…”
mentioning
confidence: 99%